Discharge Capacity of Labyrinth Side Weir Located on a Straight Channel - Emiroglu, M. Emin; Kaya, Nihat; Agaccioglu, Hayrullah (Asce-Amer Soc Civil Engineers, 2010)
Side weirs, also known as lateral weirs, are flow diversion devices widely used in irrigation as a head regulator of distributaries and escapes, land drainage, and urban sewage systems. The studies on the subject have been generally focused on rectangular and triangular side weirs located on a straight channel. However, the same is not true for labyrinth side weirs. The current studies deal with sediment transport and scour problems around side weirs and lateral structures. The investigation of the hydraulic effects of labyrinth side weirs to increase discharge capacity of them has been studied in this particular work. In the study, 2,830 laboratory tests were conducted for determining discharge coefficient of labyrinth side weirs, and results were analyzed to find the influence of the dimensionless weir length L/b, the dimensionless effective length L/l, the dimensionless weir height p/h(1), triangular labyrinth side weir included angle theta, and upstream Froude number F-1 on the discharge coefficient, water surface profile and velocities in the channel along the side weir. It has been found that discharge coefficient of labyrinth side weirs gives pretty higher coefficient value compare to that of classical side weirs and a reliable equation for discharge coefficient of labyrinth weirs is presented. Discharge coefficient of the labyrinth side weir is 1.5-4.5 times higher than rectangular side weir.
Keywords: Side-weir; Water discharge; Discharge coefficient; Intake; Labyrinth weir; Channel flow